(untitled) (Bangladesh Journal of Medical Science, 2024)
Objectives: This study aimed to analyze the global profile of the nucleotide/nucleoside analogs (NAs) for chronic hepatitis virus therapy-related research. Background: NAs, which closely resemble the structure of naturally occurring nucleotides/nucleosides, function by disrupting the elongation of the nascent DNA strand. These compounds are considered safe and well-tolerated, as they specifically target viral, but not human, polymerases involved in DNA replication. NAs are crucial in treating viral infections, including hepatitis, and are widely used due to their efficacy and safety. However, a study about trends in NAs for chronic hepatitis therapy-related research was never reported before. Methods: The NAs for chronic hepatitis therapy-related research bibliometric analysis was performed on articles indexed in the Scopus database from 1986 to 2022. Results: The total number of articles published worldwide is 2,341 documents, with an annual average of 65 documents. The United States generated the most articles (n = 486), followed by China (n = 454), France (n = 191), and Italy (n = 179). Since 1992, the number of publications has increased dramatically worldwide. Globally, liver cell carcinoma, antiviral therapy, hepatitis B (e) antigen, and alanine aminotransferase are becoming hot research topics in the field. Conclusions: This study provides a unique composite picture of NAs for chronic hepatitis therapy-related research worldwide and evaluates research productivity from 1986 to 2022. This finding suggests that the prospects for interventions in chronic hepatitis remain promising. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 747-756